Geodetic constraints to the source mechanism of the 2011–2013 unrest at Campi Flegrei (Italy) caldera. Issue 10 (26th May 2015) - Trasatti, Elisa; Polcari, Marco; Bonafede, Maurizio; Stramondo, Salvatore
Abstract Campi Flegrei caldera (Italy) was affected by a new unrest phase during 2011–2013. We exploit two COSMO‐SkyMed data sets to map the deformation field, obtaining displacement rates reaching 9 cm/yr in 2012 in the caldera center. The resulting data set is fitted in a geophysical inversion framework using finite element forward models to account for the 3‐D heterogeneous medium. The best fit model is a north dipping mixed‐mode dislocation source lying at 5 km depth. The driving mechanism is ascribable to magma input into the source of the large 1982–1984 unrest (since similar source characteristics were inferred) that generates initial inflation followed by additional shear slip accompanying the extension of crack tips. The history and the current state of the system indicate that Campi Flegrei is able to erupt again, and the advanced techniques adopted provide useful information for short‐term forecasting.